Pulsed-Field gel electrophoresis: protocols - Rappold, Gudrun; Ried, Karin; Klink, Albrecht; Rao, Ercole; Weiß, Birgit (Techniques in molecular medicine, 1999)
Pulsed-field gel electrophoresis (PFGE) techniques in combination with the cloning of large fragments of DNA into yeast artificial chromosomes (YACs) have revolutionized physical mapping in molecular genetics (Barlow and Lehrach 1987; Burke et al. 1987). DNA contigs of megabase length and physical maps of chromosome bands or entire human chromosomes are now at the stage of feasibility.
Gesehen am 06.04.2021